Pengaruh Digital Marketing terhadap Keputusan Pembelian Online - Prisma Miardi Putri; R.A Marlien (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
Shopee is an online marketplace application, shopee offers a variety of products such as electronics, mother and child needs, fashion, make up and skin care, even fresh vegetables are sold at shopee. This study aims to examine the effect of digital marketing, influencer marketing and online customer reviews on online purchasing decisions. The objects used in this study are Shopee e-commerce users. The sampling technique used is proportional sampling method with 120 respondents. Data analysis uses multiple regression and it is found that digital marketing, influencer marketing online customer reviews have a significant effect on online purchasing decisions.